臺灣產蘚類植物生物地理研究 - 蔣鎮宇 (國立臺灣師範大學生命科學學系, 2014)
臺灣蘚類植物誌的特色為具高的物種歧異度及較低的特有物種比例，除了其中49%的泛分佈種之外，臺灣的蘚類誌與日本、中國有非常高的相似性（30%），此外，分佈於中南半島、喜馬拉雅山及熱帶亞洲的物種更增加了本島蘚類物種的複合性；雖然長距離孢子傳播極其可能，一般植物誌的組成則仍與鄰近地區類似，臺灣與南中國之間高的物種相似性，顯示孢子傳播與距離成反比並受限於物理的限制。 臺灣黑蘚植物，一群高山寒原物種，的高歧度可歸因於其具兩個不同的起源，亦即一來自中國大陸，一如王氏黑蘚等，以及另一來自熱亞洲，一如多型黑蘚等等；高歧異度的另一原因則為較高比例的特有物種，其中之一的玉山黑蘚與王氏黑蘚代表可能源自喜馬拉雅山區的物種，而另一臺灣黑蘚則可能種化自來自熱帶亞洲的祖先物種。 本文比較64種東亞鳳尾蘚植物，其為一泛世界分佈屬而生長於本島中低海拔地區，其中23種泛分佈。而26.6%為As2地區特有，11種主要分佈於As3 地區的種類構成中國南部及西南部植物誌的要素，而4種分佈於熱帶亞洲的物種主要生長於海南島及臺灣的甯K半島。另一物種，東亞昂氏蘚，則為臺灣中高海拔箭竹草原的物種，且不連續分佈於臺灣及西南中國等地，此一個體矮小的種類生態與一再發生的草原火災有極高的相關，推測其演化歷史可溯及最後一次冰河徹退，與優勢物種玉山箭竹及高山芒有共同演化的關係。 兜葉蘚屬則為另一顯現臺灣及南中國高度相關的低海拔物種，全世界有三種，局限分佈於臺灣、中國南部、越南及菲律賓，而在海南島交會，其中分佈於臺灣及中國南部的兜葉蘚分佈於其以西地區的杜氏兜葉蘚則為帶蘚科分佈的北限。 臺灣蘚類植物誌具有高度分歧及多起源的特性，除了泛分佈種外，大部分的組成物種則局限於東亞地區。而分佈於喜馬拉雅山─西南中國─臺灣一線的物種可能代表的是植物地理及地質的歷史。 Moss flora of Taiwan is characterized by high species density and low level of endemism. Except for the widespread species (49.4%), moss flora of Taiwan shares the highest identity (30.3%) with Japan and China. Nevertheless, taxa that are also distributed in Indochina, Himalayas and tropical Asia add the complexity of the moss flora of this island. Although long-distance dispersal of spores in mosses is possible, the floristic composition is rather related between neighboring areas. High floristic similarity, which appears proportional inversely to geographical distance, between Taiwan and South China reveals physical constraint on spore dispersal in average taxa. High diversity in Andreaea, a taxon growing at alpine tundra, of Taiwan may be ascribed to two different origins of its composing taxa: namely one from mainland China, including A. wangiana, and the other from tropical Asia, including A. mutabilis. The Himaland origin hypothesis is not only supported by the distribution pattern of A. wangiana but also by another alpine genus, Pseudopleuropus. Species of Fissidens, a worldwide genus distributed in low and middle elevations of this island, of east Asian countries are compared. Among the 64 total species, with 23 species being widespread 26.6% taxa are ...